2016
DOI: 10.1111/gbi.12219
|View full text |Cite
|
Sign up to set email alerts
|

Primary productivity of snow algae communities on stratovolcanoes of the Pacific Northwest

Abstract: The majority of geomicrobiological research conducted on glacial systems to date has focused on glaciers that override primarily carbonate or granitic bedrock types, with little known of the processes that support microbial life in glacial systems overriding volcanic terrains (e.g., basalt or andesite). To better constrain the role of the supraglacial ecosystems in the carbon and nitrogen cycles, to gain insight into microbiome composition and function in alpine glacial systems overriding volcanic terrains, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 108 publications
(145 reference statements)
10
71
0
Order By: Relevance
“…In contrast, Fujii et al 26 attributed Antarctic snow-alga distribution and abundance to allochthonous bird deposition of limiting nutrients. A field microcosm study on North American volcanoes 27 found no NP-enrichment effect on snow-alga abundance, while a laboratory microcosm of Greenland cryoconite debris 17 showed NPenrichment doubled both organic carbon and chlorophyll-a. Here, the response to NPK-enrichment in 2-m 2 plots exceeds the mean response of approximately 3.4× reported for pelagic phytoplankton in NP-enriched freshwater lakes 28 .…”
Section: Nutrients and Water Limit Snow-alga Abundancementioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, Fujii et al 26 attributed Antarctic snow-alga distribution and abundance to allochthonous bird deposition of limiting nutrients. A field microcosm study on North American volcanoes 27 found no NP-enrichment effect on snow-alga abundance, while a laboratory microcosm of Greenland cryoconite debris 17 showed NPenrichment doubled both organic carbon and chlorophyll-a. Here, the response to NPK-enrichment in 2-m 2 plots exceeds the mean response of approximately 3.4× reported for pelagic phytoplankton in NP-enriched freshwater lakes 28 .…”
Section: Nutrients and Water Limit Snow-alga Abundancementioning
confidence: 98%
“…A single pulse of N-enrichment in-frame at the start of interval photography on the Eklutna Glacier also suggested a response of red-snow algae to nutrient enrichment, with earlier, more intensely red-coloured snow at and near the enrichment point (Supplementary Movie). Previous field observations 16,26 and in vitro microcosm nutrient additions 17,27 suggest that nutrient limitation in snow algae is study-dependent. For example, Lutz et al 16 in a wide-ranging Arctic study found no correlation between alga abundance and nutrient concentrations in filtered red snow.…”
Section: Nutrients and Water Limit Snow-alga Abundancementioning
confidence: 98%
“…Eliot Glacier is a 1.6-km 2 glacier on the northeast flank of Mt. Hood adjacent to and partly overlying dacitic block and ash flows (Crandell, 1980;Hamilton & Havig, 2017;Jackson & Fountain, 2007).…”
Section: Field Sitesmentioning
confidence: 99%
“…With habitat regression, or if areas of snow melt completely early in the summer, the ecosystem may be lost entirely for that season (Convey, 2011;Anesio et al, 2017). Whichever outcome prevails which is likely to vary with locationthere is an urgent need to study these polar communities to provide a balanced view of polar terrestrial biodiversity and to avoid the loss of these extremophilic primary producers and their community structure at both local and continental scales (Williams et al, 2003;Rogers et al, 2007;Hamilton & Havig, 2017;Rintoul et al, 2018). This is especially pertinent because, although snow algae may not be endemic, there is evidence of endemism and long-term evolutionary isolation in other associated microbial species and communities around Antarctica, probably due to the geographical isolation of the continent (Vyverman et al, 2010;Remias et al, 2013;Cavicchioli, 2015;Petz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%